Petrological Characteristics, Geological Development History, and Heritage Value of Typical Geological Features in the Vietnam South Central Region - Tuan, Nguyen Van; Nghi, Tran; Thanh, Dinh Xuan; Thu, Trinh Hoai; Nhan, Tran Thi Thanh; Dung, Tran Thi; Trang, Nguyen Thi Huyen; Dong, Nguyen Van; Thuy, Trinh Thi; An, Nguyen Thi Hien; Tuyen, Vu Van; Huong, Tran Thi Thuy (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2DO - 10.25073/2588-1094/vnuees.5354, 2025)
During the Cenozoic, there are two types of basalts in the South Central region: Effusive basalts and explosive basalts. Effusive basalts include: i) Alkaline basalts with phenocrystal texture consisting of major minerals such as albite, augite, olivine, and sanidine. The basement has a hyalopilitic texture with sub-parallel albite microlites embedded in a volcanic glass. These characteristics demonstrate that magma partially melted in the deep lower part of the upper mantle; and ii) The tholeiitic basalts, which contain no phenocrysts, display a pilotaxitic groundmass texture dominated by obliquely extinguished mafic plagioclase microlites, suggesting derivation of the magma from the upper part of the upper mantle. The eruption of underwater basalts creates columnar shapes. The phenomenon of basalt explosions has carved out unique landscapes like basalt tuff layers, volcanic lakes, and complex cave systems. The stages of sea level rise in the Quaternary when the Earth warmed up, have carved marine notches and abrasive terraces at height from 60 m to 5 m. The interaction between endogenic and exogenic geological processes has shaped a diverse geological landscape of high scientific, aesthetic, and educational value and offering strong potential for development as a UNESCO Global Geopark in the Vietnam South Central region.